Hydroxysafflor Yellow A Exerts Anti-Inflammatory Effects Mediated by SIRT1 in Lipopolysaccharide-Induced Microglia Activation - Qin, Xiude; Chen, Juanjuan; Zhang, Guowei; Li, Chuanpeng; Zhu, Jinqiang; Xue, Hong; Li, Jinfang; Guan, Tianxiang; Zheng, Haotao; Liu, Yu; Cai, Haobin (Frontiers in Pharmacology, 2020)
Microglia activation causes a severe neuroinflammation, contributing to the development of many diseases, yet its driving mechanism is still incompletely unknown. In the current study, we identified that Hydroxysafflor yellow A (HYA), a chalcone glycoside derived from Carthamus tinctorius L. effectively attenuates Lipopolysaccharide (LPS)-induced inflammatory response in primary microglia via regulating inflammatory genes expression and remodeling microglia polarization. We also reported the effects of HYA on improving lipopolysaccharide (LPS)-stimulated mitochondrial dysfunction and oxidative stress in microglia for the first time. Interestingly, we also found that HYA could serve as an effective SIRT1 activator. SIRT1 deficiency abrogates the protective effects of HYA against LPS-induced noxious responses. Overall, our data suggest that HYA, as a novel SIRT1 activator, could be an effective treatment for neuroinflammation in neurodegenerative diseases.